Say no to Arthritis : the proven drug free guide to preventing and relieving arthritis - Holford, Patrick (Judy Piatkus LondonGB, 1999)
Advises on natural approaches to preventing and relieving symptoms of arthritis and associated conditions including osteoarthritis, fibromyalgia, and polymyalgia. Explains what arthritis is and identifies factors that contribute to its development. Explores the role of diet, vitamins, minerals and natural supplements e.g. glucosamine sulphate and chondroitin in the prevention and treatment of arthritis. Looks at the dangers of conventional cortisone and NSAID drugs, and provides an anti-arthritis diet and recipes. Advises on posture; identifying and eliminating allergens; exercise; and, stress reduction.